Effectiveness of The Digital Government System in Correspondence Process - Fitriyana, Desi; Purnamasari, Irma; Ramdani, Faisal Tri (Public Policy Journal, 2025)
Digital government is a form of digital technology transformation in the public sector, implemented by the National and Political Unity Agency of Bogor Regency through a digital correspondence system. This system is designed to efficiently manage the inflow and outflow of information. The innovation was initiated in response to issues such as slow correspondence processes, excessive paper usage, time inefficiency, and high costs. This study aims to examine the effectiveness of the digital government system in the correspondence process at Bakesbangpol Bogor Regency. The research method used is descriptive quantitative, with data collected through questionnaires and interviews. The sample consisted of 73 members of the public and 27 civil servants (ASN). Data analysis was conducted descriptively using effectiveness indicators based on the dimensions of bureaucracy, neoinstitutionalism, networks, and governance. The results show that the implementation of the digital government system is generally considered good. From the perspective of civil servants, effectiveness is rated very good with an average score of 4.71, while from the public, it is rated good with an average score of 3.91. However, the overall effectiveness score is still considered moderate, at 2.95. The bureaucracy dimension received the highest score from ASN, while the public rated the neoinstitutionalism dimension as the best. Conversely, the network dimension received the lowest rating from the public. This study concludes that although the digital government system has been implemented well, improvements are still needed in terms of bureaucracy and network aspects, enhancement of infrastructure, and inter-agency coordination to increase theeffectiveness of the digital correspondence system at Bakesbangpol Bogor Regency.